Clinical applicability of undifferentiated mesenchymal stem cells from adipose tissue for bone regeneration surgeries of the atrophic maxilla and mandible (Research, Society and Development, 2021)
Objectives: This literature review aimed to perform a strategic search for scientific articles on the applicability of adipose tissue stem cells associated with grafts in bone regeneration surgeries in the maxilla and atrophic mandible. Methodology: A search strategy was carried out in four databases (PubMed, Embase, Web of Science and Cochrane Library) by crossing different descriptors according to the PICO strategy. Results: 206 articles were obtained, however according to the inclusion and exclusion criteria of this review, a total of 9 articles were selected for a critical and analytical analysis. The results of articles from this review showed that for obtaining mesenchymal stem cells (MSCs) from adipose tissue, it can be collected from abdominal tissue (TA) or by buccal fat pad (BB). Studies that carried out the characterization of the cells present in the adipose tissue result in expression of markers of mesenchymal cells. For transplantation in a clinical approach, surgeries for maxillary sinus grafting, bone regeneration for atrophic premaxilla and mandible, as well as condyle fracture, demonstrated good outcomes when MSCs or the stromal vascular fraction (SVF) were associated with autogenous, alloplastic, allogenic or xenogenic grafts. Conclusion: According to the limited scientific evidence, the cellular approach with SVF and CTMs derived from TA or BB prove to be safe and effective when associated with autogenous, alloplastic, allogenic or xenogenic grafts, improving the osteogenic potential in bone regeneration surgeries.